Optimizing the Design of Surface-Acoustic-Wave Ring Resonator by Changing the Interdigitated Transducer Topology - S. Yu. Shevchenko; D. A. Mikhailenko; B. Nyamweru (Известия высших учебных заведений России: Радиоэлектроника, 2021)
Introduction. Previous works considered the frequency characteristics and methods for fixing sensitive elements in the form of a wave ring resonator on surface acoustic waves in a housing made of various materials, as well as the influence of external factors on sensitive elements. It was found that the passband in such a case is sufficiently wide, which can affect adversely signal detection when measuring acceleration using the sensitive element under development. Therefore, it has become relevant to reduce the sensitive element’s bandwidth by changing the design of the interdigitated transducer (IDT).Aim. To demonstrate an optimal topology for an IDT with a low bandwidth, leading to improved signal detection when acceleration affects the sensitive element.Materials and methods. The finite element method and mathematical processing in AutoCAD and in COMSOL Multiphysics.Results. Nine topologies of IDT are proposed. All these types were investigated using the COMSOL Multiphysics software on lithium niobate substrates, which material acts as a sensitive element. The frequency characteristics are presented. The data obtained allowed an optimal design of the ring resonator to be proposed: an IDT with rectangular pins without selective withdrawal.Conclusion. Self-generation in a ring resonator can be performed by withdrawing no more than one pair of IDTs for 10 or more periods. In this case, the withdrawal of IDTs should be uniform. With an increase in the number of IDT withdrawals, the geometry of the ring resonator is violated, and the wave leaves the structure. The presence of a shared bus keeps the surface acoustic wave inside the IDT structure, and the narrowing of the periods towards the inner part of the structure makes it possible to improve the frequency characteristics of the ring resonator on surface acoustic waves.